Pilot in-field food safety training assessment of donation gardens managed by Master Gardeners in Iowa - Shannon Coleman; Smaranda Andrews; Bridget Perry; Ann Williams (Urban Food Systems Symposium, 2020)
Lack of access to safe, healthy food is a significant concern. Many non-profit organizations, such as local food pantries, are exploring ways to increase access to fresh produce in both rural and urban areas. Due to the vulnerability of the target audience that frequents the pantries, gardeners must distribute fresh produce that is safe to eat and free of pathogens. The vulnerable population includes young children, immunocompromised people, older adults, and pregnant women. The objective of this study was to assess Master Gardeners’ (n=39) awareness, knowledge, and attitude following a pilot in-field food safety training on managing donation gardens. Each hands-on activity in the training was designed to teach gardeners the importance of reducing risk in the garden. To evaluate the training, the team adopted a three-stage process: 1) Qualitative research to learn more about Master Gardeners’ perceptions of food safety and their motivations for engaging in the volunteer activity, used to inform workshop development, 2) Pre/post measurement of changes in awareness, knowledge, and attitude at the time of the workshop, and 3) Measurement of any changes in the practice of key food safety protocols two to three months post-workshop. The evaluation results showed that knowledge increased significantly after the gardeners participated and completed hands-on activities. For example, we observed that the gardeners gained significant knowledge regarding what items were crucial in a food safety tool kit. The post-training follow-up evaluation indicated that participants made significant changes too many but not all of their practices. However, gardeners purchased items to help them implement food safety practices in donation gardens throughout Iowa.
Keywords: produce safety; hands-on activities